An Analysis of Transitive and Intransitive Phrasal Verb from Harry Potter and the Chamber of Secrets Chapter 1-5 - Meidi Kulsum, Eva; Fauziah , Fani (UIN Sunan Gunung Djati Bandung, 2025)
This research aims to analysis the transitive and intransitive verb from Harry Potter and the Chamber of Secret Novel Chapter 1-5. This research used descriptive qualitative method to gain the data. There are 38 phrasal verbs classified based on those that have direct objects and those that do not have direct objects in their sentences. This study shows that there are 28,95% transitive verbs along with 71,05 phrasal verbs used by the author in the Harry Potter and the Chamber of Secrets novel page 1-110. This highlights a significant preference for the use of phrasal verbs in emphasizing action or changing the meaning of a word when a particle has been added. Transitive Phrasal Verb such as pick up, put on, and take off are used to indicate actions involving direct object, while Intransitive Phrasal Verb such as got up, went down, and come in describe actions without direct object. This analysis shows that the use of phrasal verb in novel has various idiomatic meanings that cannot always be translated literally, and this not only enriches the language style but also reflects the dynamics of the characters in the narrative situation. This finding is expected to contribute to the understanding of English grammatical structure, especially in the learning and translating literary works.